Solving System of Linear Fredholm Integral Equations of Second Kind Using Open Newton-Cotes Formulas - Ibraheem, G. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, the linear system of Fredholm integral equations is solving using Open Newton-Cotes formula, which we use five different types of Open Newton-Cotes formula to solve this system. Compare the results of suggested method with the results of another method (closed Newton-Cotes formula) Finally, at the end of each method, algorithms and programs developed and written in MATLAB (version 7.0) and we give some numerical examples, illustrate suggested method